2022
DOI: 10.1038/s41598-022-24563-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of violet–blue light to inactive microbial growth

Abstract: The increase in health care-associated infections and antibiotic resistance has led to a growing interest in the search for innovative technologies to solve these problems. In recent years, the interest of the scientific community has focused on violet–blue light at 405 nm (VBL405). This study aimed to assess the VBL405 efficiency in reducing microbial growth on surfaces and air. This descriptive study run between July and October 2020. Petri dishes were contaminated with P. aeruginosa, E. coli, S. aureus, S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Overall, the inactivation results suggested that continuous 405 nm LED exposure for up to 48 h can effectively inactivate various foodborne pathogens. Since 405 nm blue light has been shown not to have any long term detrimental effect on mammalian cells, this treatment can become a useful tool for controlling microbial contamination in food processing and handling facilities without posing a risk to human health 22 , 23 , 48 . Unlike conventional UV and PL technologies, which are subject to strict regulatory limits for use in food applications 49 51 , 405 nm blue light can be used at high doses without causing toxicity to humans operators.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the inactivation results suggested that continuous 405 nm LED exposure for up to 48 h can effectively inactivate various foodborne pathogens. Since 405 nm blue light has been shown not to have any long term detrimental effect on mammalian cells, this treatment can become a useful tool for controlling microbial contamination in food processing and handling facilities without posing a risk to human health 22 , 23 , 48 . Unlike conventional UV and PL technologies, which are subject to strict regulatory limits for use in food applications 49 51 , 405 nm blue light can be used at high doses without causing toxicity to humans operators.…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian cells are not sensitive to VBL and aBL like bacterial ones, so this light in antimicrobial doses is safe for humans. Endogenous DNA does not absorb VBL and aBL; thus, there is no damage to it, and this light also does not damage materials, so it is used, for example, to disinfect medical instruments in hospitals [60,61]. The mechanism of endogenous indirect photoinactivation has not been fully explicated, but it is generally accepted that the wavelengths of VBL and aBL overlap with absorption bands of endogenous chromophores in microbial cells, such as flavins, porphyrins, bilirubin, or chlorophyll.…”
Section: Antimicrobial Photoinactivationmentioning
confidence: 99%
“…These endogenous chromophores are photosensitizers (PSs) because after the absorption of visible light photons, they can transfer energy to nearby oxygen molecules, producing singlet oxygen ( 1 O2) and other reactive oxygen species (ROS) (through electron/proton transfer), which can damage intracellular constituents (by reacting with proteins, lipids, and nucleic acids), such as damage to the membranes and the DNA cleavage, leading to cell death [61][62][63][64]. The presence of endogenous porphyrins has been identified in aBL sensitive strains of OPPPs (P. aeruginosa, A. baumannii, H. pylori) and is associated with demonstrated inactivation of their planktonic cells and biofilms by aBL [61][62][63][64]. In the case of H. pylori, protoporphyrin IX (PPIX) and coproporphyrin (CP) were determined by Endogenous indirect photoinactivation (Figure 3) is based on the action of visible light, especially the purple and blue parts of the spectrum that are commonly referred to as antimicrobial blue light (aBL) and violet-blue light (VBL).…”
Section: Antimicrobial Photoinactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lately, near-UVA (405-nm) has emerged as a potential alternative treatment for localized infections and environmental decontamination (8). UV-C and near UVA irradiation are the most widely used light disinfection methods, with the latter being less detrimental to host cells (9). Near-UVA, particularly of the 405 nm wavelength, exerts its antimicrobial effects through excitation of endogenous intracellular light receptors such as porphyrins and flavins (10) which then undergo an energy transfer process that leads to generation of reactive oxygen species (ROS) resulting in lipid peroxidation, DNA damage, https://doi.org/10.1017/S0950268823000560 Published online by Cambridge University Press experiment, consisted of 4 vertical supports, each 40 cm high, and a 36x36 cm wide wooden base the same size as the ceiling lamp used for the test.…”
Section: Introductionmentioning
confidence: 99%